Asuhan Kebidanan Pranikah Dalam Pemberian Imunisasi Tetanus Toxoid (TT) Pada Calon Pengantin Di Puskesmas Mapaddegat Kabupaten Kepulauan Mentawai - Marita Ronitua Sinabariba; Dina Ayuning Tyas; Yohana Suganda (Jurnal Medisains Kesehatan, 2026)
Premarital health care is a promotive and preventive effort to improve reproductive health and prepare for a healthy pregnancy. One important intervention is the provision of Tetanus Toxoid (TT) immunization to prevent maternal and neonatal tetanus. This study aims to describe premarital midwifery care in providing TT immunization to prospective brides and grooms at the Mapaddegat Community Health Center in the Mentawai Islands Regency. The method used is a case study with a descriptive approach to one prospective bride aged 24 years. Data collection was carried out through anamnesis, physical examination, and supporting examinations. The results of the assessment showed that the client had an incomplete TT immunization status. The midwifery care provided included preconception health education, TT immunization counseling, and immunization administration according to procedures. After the intervention, the client understood the importance of TT immunization and was willing to continue immunization as scheduled. Comprehensive premarital midwifery care has been proven to play a role in increasing the knowledge and readiness of prospective brides and grooms in facing pregnancy. Therefore, the role of health workers, especially midwives, is very important in increasing the coverage of TT immunization as an effort to prevent tetanus in mothers and babies.